Public service media under pressure - Arriaza Ibarra, Karen (Javnost (Ljubljana), 2014)
The current economic crisis is global in scope, thus affecting both countries in the North and in the South. As a consequence, national European governments are modifying their policies in order to cut down on public spending. This article compares how public service media policies are shaped in this new situation in two countries that represent very contrasting models of public service media: Spain and Sweden. The story of public service media survival in times of rapid development of media technology and liberal political hegemony is a common theme in contemporary media and communication research. This study adds to this theme, by exploring the conditions for public service media further by a more explicit focus on how newly elected governments approach public service media policies in times of economic crises. The basic aim of the study is to compare how public service media conditions may change in countries with very diff erent public service media models.
Keywords: mass media; množični mediji; communication; komuniciranje; komunikacijska tehnologija; ekonomska kriza; Spain; Španija; Švedska